2017
DOI: 10.1590/1234-56781806-94790550201
|View full text |Cite
|
Sign up to set email alerts
|

Heritage and Patrimony of the Peasantry Framework and Rural Development Indicators in Rural Communities in Mexico

Abstract: Abstract:The analytical framework "heritage and patrimony of the peasantry" and its recommended implementation theoretically provide an enhancement over previous methodologies to examine rural development. The current paper measures rural development indicators in six Mexican rural territories, and analyses their interaction in the heritages and patrimonies of the peasantry. The principal indicators that affect the patrimonies in these regions were recognised as Pluriactivity, Social Acknowledgment, Biodiversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 22 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, Culture is identified as the source of motivation for collective work. However, it has been observed that the problems relating to the loss of identity, diversity and culture are problems forgotten by public policy, which constitutes the strongest threat affecting the peasantry [ 134 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Culture is identified as the source of motivation for collective work. However, it has been observed that the problems relating to the loss of identity, diversity and culture are problems forgotten by public policy, which constitutes the strongest threat affecting the peasantry [ 134 ].…”
Section: Resultsmentioning
confidence: 99%
“…The same happens with rural development, which originally represents 13.4% of the references according to Table 5 , but its implications can be extended to other visions as found in Refs. [ 83 , 85 , 87 , 88 , 100 , [112] , [113] , [114] , [115] , [116] , [117] , [118] , 134 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is produced by peasants, small, medium and large farmers, as well as by multinational food companies. This monoculture, which is indeed well-paid, has increased the incomes of many people (input sellers, transporters, harvesters, and packers) who are directly and indirectly related to production (Pachón et al, 2017b).…”
Section: Rural Territorymentioning
confidence: 99%
“…This means that the peasantry must internally identify its needs according to the particular circumstances of each community. This concern is paramount because the generalization of problems and solutions has shown poor results in many rural places (Pachón et al, 2017a;2017b)…”
Section: Quality Of Life and Respect For Human Rightsmentioning
confidence: 99%